Analysis of Financial Performance Based on Economic Value Added at PT Ultrajaya Milk Industry & Trading Company Tbk - Vinsensius Kenzie Aldo Baswara; Nazwa Yuwandira Putri; Siti Rahmah; Fharda Nur Khasanah; Nabila Ammarah Dani; Ma'isyatur Rodhiyah; Yossinomita Yossinomita (Jurnal Administrasi Terapan, 2026)
This study aims to analyze the financial performance of PT Ultrajaya Milk Industry & Trading Company Tbk using the Economic Value Added (EVA) method during the 2015-2025 period. This study uses a quantitative descriptive approach with secondary data obtained from the company's annual financial statements. The analysis technique was carried out through calculations of the effective tax rate, Net Operating Profit After Tax (NOPAT), Invested Capital, Weighted Average Cost of Capital (WACC), Capital Charge, and Economic Value Added. The results show that all EVA values during the 2015-2025 period were positive. The lowest EVA value occurred in 2015 at 291,705 billion Rupiah , while the highest EVA value occurred in 2025 at 753,870 billion Rupiah . These findings indicate that the company is able to generate operating profit after tax that exceeds the cost of capital used. Thus, PT Ultrajaya Milk Industry & Trading Company Tbk can be assessed as capable of consistently creating economic value added for shareholders during the research period. Keywords: Economic Value Added; Financial Performance; NOPAT; WACC; Capital Charge